Síntomas de trastornos afectivos y emocionales como consecuencia del COVID-19 en docentes del departamento del Atlántico (2022)
The COVID-19 pandemic has caused not only physical but also psychological and emotional consequences in those who have been directly or indirectly impacted by the virus. The teaching population was one of the groups in which most change was generated as a result of the pandemic; moving to a new way of working from home, not being able to place limits between work schedules and work spaces and at the same time, having to comply with household chores. The objective of this research is to identify the psychological effects caused by the COVID-19 pandemic on teachers in the department of Atlántico. In order to obtain the data, a population sample of 78 teachers was used, the information was collected by means of a form composed of sociodemographic questions, questions aimed at knowing the levels of motivation and questions to know the modifications they had in their work due to the pandemic, Beck's Hopelessness Inventory and SCL-90. Results: it was found that anxiety, depression and stress, manifested in somatization, are more evident in women than in men, likewise, it is observed how the motivation of teachers has been affected as a result of the pandemic, showing that it has decreased compared to before the pandemic, and it is also identified which factors influence the decrease in motivation.